Aggregates Morphologies of Poly(g-benzyl L-glutamate)-graft-poly(ethylene glycol) and Poly(g-benzyl L-glutamate) Mixtures in Dilute Solution - Zhu, Guo-Quan; Wang, Fa-Gang; Su, Chang-Hong; Gao, Qiao-Chun; Liu, Yu-Ying (Asian Journal of Chemistry, 2013)
Poly(g-benzyl L-glutamate) (PBLG) homopolymer and poly(g-benzyl L-glutamate)-graft-poly( ethylene glycol) (PBLG-graft-PEG) copolymer were synthesized by a standard N-carboxyl- g-benzyl-L-glutamate anhydride method and by ester exchange reaction, respectively. The aggregates morphologies of PBLG-graft-PEG and PBLG mixtures in dilute solution were studied by scanning electron microscopy. The effects of the weight (wt) ratio of PBLG-graft-PEG to PBLG, various solvent system and the addition of denaturant acid on the aggregates morphologies of the PBLG-graft-PEG and PBLG mixtures in the dilute solution were investigated.